Review of acoustical and optical techniques to measure absolute salinity of seawater - Le Menn, Marc; Nair, Rajesh (Frontiers in Marine Science, 2022)
The salinity of seawater is of fundamental importance in climate studies, and the measurement of the variable requires high accuracy and precision in order to be able to resolve its typically small variations in the oceans with depth and over long-time scales. This is currently only possible through the measurement of conductivity, which has led to the definition of a Practical Salinity scale. However, seawater is also composed of a large number of non-conducting substances that constitute salinity anomalies. Differences of the ratios of the constituents of sea salt from the Reference Composition may also change salinity anomalies. The establishment of formulae for calculating the thermodynamic properties of seawater has led to the definition of the concept of Absolute Salinity (SA), which includes such anomalies and is similar in approach to the notion of density. Although the routine in situ measurement of SA is still a huge challenge, numerous developments based on acoustic techniques, but above all, refractometry, interferometry or complex fiber optic assemblies, have been tested for this purpose. The development of monolithic components has also been initiated. The measurement of the refractive index by these techniques has the advantage of taking into account all the dissolved substances in seawater. This paper reviews the difficulties encountered in establishing theoretical or empirical relations between SA and the sound velocity, the refractive index or the density, and discusses the latest and most promising developments in SA measurement with a particular focus on in situ applications.